Preparation method of ultra-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing
Through additive manufacturing technology, the biomimetic microstructure is printed and superhydrophobic nanofillers are embedded, combined with the strategy of KH550 as a molecular bridge, the problems of poor durability and insufficient multifunctional protection of superhydrophobic materials are solved, and the preparation of ultra-durable bionic heterogeneous superhydrophobic surfaces and the possibility of complex three-dimensional curved surfaces are realized.
Patent Information
- Application Number
- CN202510074737.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing superhydrophobic materials have poor durability, which is difficult to meet the needs of complex three-dimensional curved surface application scenarios, and are not fully functional and protective.
Using additive manufacturing technology, the biomimicry microstructure of Ti6Al4V alloy is printed through laser powder bed melting technology, and superhydrophobic nanofillers are embedded in its space. KH550 is used as a molecular bridge to connect silica nanoparticles and polytetrafluoroethylene to form an ultra-durable bionic heterogeneous superhydrophobic surface.
It has achieved the preparation of ultra-durable bionic heterogeneous superhydrophobic surfaces, with excellent self-cleaning, low friction, corrosion resistance and other characteristics. It can maintain superhydrophobic performance after 5000 sandpaper wear and 200% compression strain, and is suitable for complex three-dimensional curved surface applications.
Smart Images

Figure CN119526750A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of super-hydrophobic materials, and in particular relates to a method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing. Background Art
[0002] As a new type of functional protective material, superhydrophobic material has the characteristics of self-cleaning, low friction, corrosion resistance, anti-icing, anti-fog, droplet manipulation, etc. However, the poor durability of superhydrophobic materials seriously limits the application and development of superhydrophobic materials, especially for metal or alloy materials, which often face problems such as surface contamination, surface wear, corrosion failure, etc. in practical applications.
[0003] At present, researchers have proposed a variety of super-hydrophobic strategies, which can be roughly divided into three types. The first is to achieve super-hydrophobicity of metals or alloys through laser processing, chemical etching, electrodeposition, etc. However, the super-hydrophobicity achieved by these methods depends on the synergistic effect of high-roughness micro-nano surface structure and chemical modification. These fragile micro-nano structures are usually difficult to resist mechanical wear, impact and other external forces, making the actual life of super-hydrophobic materials often lower than expected. The second is a bionic self-repairing strategy. This self-repairing super-hydrophobic material can repair the damaged surface by responding to changes in external conditions such as temperature, ultraviolet rays, humidity, etc., thereby restoring its super-hydrophobic properties. However, this strategy will cause the discontinuity of the super-hydrophobicity of the material due to the time required for repair. The third is to increase durability by adding inherently wear-resistant substances to the super-hydrophobic coating, but this method is affected by the weak characteristics of the coating itself, and the improvement of durability is still limited, and it still faces the risk of failure when facing extreme conditions. In addition, these methods also face a common problem at the same time, which is the lack of the ability to form complex three-dimensional surfaces, and it is difficult to meet the needs of complex surface application scenarios.
[0004] As an advanced manufacturing technology, additive manufacturing can achieve near-net-shape forming of materials by layer-by-layer accumulation, which can not only improve material utilization, but also manufacture some complex curved surface structures. At present, the preparation of super-hydrophobic materials by additive manufacturing is mainly concentrated in the non-metallic field, and there is still little research on additive manufacturing super-hydrophobic surfaces in the metal field. Based on this, we used Ti6Al4V alloy powder as printing material using laser powder bed fusion technology (abbreviated as LPBF) for the first time to prepare bionic microstructures, and further embedded super-hydrophobic nanofillers in the space generated by additive manufacturing bionic microstructures. This super-hydrophobic nanofiller is composed of hydrophobically modified silica nanoparticles and polytetrafluoroethylene, and KH550 (a silane material that is both organic and inorganic) is used as a molecular bridge between the two materials to combine the two, so that it has both the wear resistance of silica particles and the low surface energy, low friction, and corrosion resistance of polytetrafluoroethylene, and finally forms a super-durable bionic heterogeneous super-hydrophobic surface.
[0005] This ultra-durable bionic heterogeneous super-hydrophobic surface has excellent self-cleaning properties and still has super-hydrophobic properties after 5,000 sandpaper wears and approximately 200% compression strain. It also has extremely low friction coefficient and wear rate. After local friction and wear experiments, the wear marks still have super-hydrophobic properties. In addition, the corrosion current density of this ultra-durable bionic heterogeneous super-hydrophobic surface is about two orders of magnitude lower than that of the substrate, and the impedance is increased by about 17 times. This bionic heterogeneous multifunctional surface can be used in a variety of metals or alloys suitable for laser powder bed melting preparation, and has broad application prospects in aerospace, navigation, and national defense and military industries.
[0006] Therefore, providing a method for preparing an ultra-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing is in line with practical needs and is innovative. Summary of the invention
[0007] 1. Technical issues to be resolved In order to solve the problems of poor durability and insufficient multifunctional protection of super-hydrophobic materials in the prior art, the present invention provides a method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing.
[0008] (II) Technical solution In order to achieve the above-mentioned purpose, the main technical scheme adopted by the present invention includes: a method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing, comprising the following steps: Step 1: Use appropriate printing parameters and Ti6Al4V spherical powder as the material to print the bionic microstructure surface in one step; Step 2, then immersing the bionic microstructure surface in a chemical polishing solution for polishing for 90 seconds to obtain a polished bionic microstructure surface of a pre-designed size; Step 3, performing hydrophobic modification on the nano-silicon dioxide particles to obtain a modified nano-silicon dioxide dispersion; Step 4, adding polytetrafluoroethylene solution and KH550 solution to the modified nano-silicon dioxide dispersion obtained in step 3 to form a sol; Step 5, immersing the polished bionic microstructure surface obtained in step 2 into the sol of step 4, and drying after ultrasonic treatment to gel it to obtain an ultra-durable bionic heterogeneous super-hydrophobic surface.
[0009] Preferably, the bionic microstructures are triangular and arranged in a cross array to mimic the distribution of lotus leaf papillary structures.
[0010] Preferably, in step one, the specific method for printing the bionic microstructure surface is: saving the designed bionic microstructure surface model in stl. format, slicing the bionic microstructure surface model and importing it into the printing equipment control software, turning on the water cooling cycle, installing the substrate and the scraper, placing the Ti6Al4V spherical powder with a median diameter of 35 μm in the printer powder bin, and then introducing high-purity argon gas into the printing chamber. After the oxygen content in the molding chamber is lower than 0.03%, a laser power of 125 W, a scanning speed of 600 mm / s, a scanning spacing of 0.08 mm, a layer thickness of 0.03 mm, and a scanning angle of 47° are used to start preparing the bionic microstructure surface.
[0011] Preferably, in step 2, the chemical polishing solution consists of H2O, HNO3, and HF in a volume ratio of 5:1:4, the HNO3 concentration is 4 mol / L, and the HF concentration is 22.5 mol / L.
[0012] Preferably, in step three, the specific method for hydrophobic modification of nano-silica particles is: disperse 4g of nano-silica in 40ml of anhydrous ethanol, stir for 5 minutes to make it evenly dispersed, then add 1.5g of perfluorodecyltrimethoxysilane solution, and stir in a constant temperature water bath at 40°C for 2 hours to ensure that the nano-silica is fully modified.
[0013] Preferably, in step 4, the specific method for forming the sol is: adding 1.6 g of polytetrafluoroethylene emulsion and 0.5 g of KH550 solution to the modified nano-silicon dioxide dispersion obtained in step 3 to form a sol.
[0014] Preferably, in step five, the specific method for obtaining the ultra-durable bionic heterogeneous super-hydrophobic surface is as follows: immersing the polished bionic microstructure surface in a sol and ultrasonically treating it for 30 minutes, and then placing it in a drying oven at 120°C for 6 hours to fully gelate it to obtain an ultra-durable bionic heterogeneous super-hydrophobic surface.
[0015] (III) Beneficial effects The beneficial effects of the present invention are: Inspired by the lotus leaf effect, the ultra-durable bionic heterogeneous super-hydrophobic surface prepared by the present invention has ultra-durability, wherein the bionic microstructure can provide good wear resistance and reduce the damage of the nanofiller, and the nanofiller can play a reverse supporting role and reduce the fracture of the bionic microstructure; Different from the traditional super-hydrophobic surface, the present invention uses the strategy of bionic microstructure-nanofiller to realize the multifunctional protection characteristics of super-hydrophobic materials, so that it has self-cleaning, low friction, corrosion resistance and protection characteristics, effectively improving the comprehensive performance of super-hydrophobic materials; The present invention innovatively uses additive manufacturing technology to prepare a super-durable bionic heterogeneous super-hydrophobic surface, so that the metal super-hydrophobic material has the ability to form on complex three-dimensional surfaces, greatly expanding the application of super-hydrophobic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a flow chart for preparing the ultra-durable bionic heterogeneous super-hydrophobic surface in the present invention: Figure 1 1 is: LPBF printing process; 2 is: schematic diagram of bionic microstructure surface and its actual electron microscope image; 3 is: chemical polishing solution; 4 is: schematic diagram of polished bionic microstructure surface and its actual electron microscope image; 5 is: nano-silica particles; 6 is: modified nano-silica particles; 7 is: schematic diagram of sol after modified SiO2 is mixed with polytetrafluoroethylene and KH550; 8 is: ultra-durable bionic heterogeneous super-hydrophobic surface; Figure 2 It is a scanning electron microscope image of the super-durable bionic heterogeneous super-hydrophobic surface of the present invention, wherein A is: the overall microscopic morphology of the super-durable bionic heterogeneous super-hydrophobic surface; B is: the bionic microstructure morphology in the super-durable bionic heterogeneous super-hydrophobic surface; C is: the microscopic morphology of the super-hydrophobic nanofiller; Figure 3 The figures are the real objects and contact angle test diagrams of the super-durable bionic heterogeneous super-hydrophobic surface in the present invention, wherein A is the real object diagram of the super-durable bionic heterogeneous super-hydrophobic surface; B is the contact angle test of the super-durable bionic heterogeneous super-hydrophobic surface; C is the lyophobicity test of the super-durable bionic heterogeneous super-hydrophobic surface to liquids of different densities; Figure 4 1 is a diagram of the self-cleaning process of the super-durable bionic heterogeneous super-hydrophobic surface of the present invention, wherein A is a diagram of sprinkling carbon powder on the super-durable bionic heterogeneous super-hydrophobic surface; B is a diagram of the self-cleaning process of the super-durable bionic heterogeneous super-hydrophobic surface; C is a diagram of the self-cleaning process of the super-durable bionic heterogeneous super-hydrophobic surface; D is a diagram of the carbon powder on the super-durable bionic heterogeneous super-hydrophobic surface rolling off with the droplets and completely disappearing; Figure 5 A graph showing changes in the contact angle and rolling angle of the ultra-durable bionic heterogeneous super-hydrophobic surface of the present invention as the number of sandpaper abrasions increases; Figure 6 It is a graph showing the changes of the contact angle and the rolling angle of the ultra-durable bionic heterogeneous super-hydrophobic surface as the compression displacement increases in the present invention; Figure 7 This is a graph showing the variation of the friction coefficient of the super-durable bionic heterogeneous super-hydrophobic surface under a load of 1N with the friction time in the present invention; Figure 8 This is a graph showing the variation of the friction coefficient of the super-durable bionic heterogeneous super-hydrophobic surface under a load of 5N with the friction time in the present invention; Fig. 9 This is a graph showing the variation of the friction coefficient of the super-durable bionic heterogeneous super-hydrophobic surface under a load of 10N with the friction time in the present invention; Fig.10 This is an actual picture of super-hydrophobicity at the wear marks of the super-durable bionic heterogeneous super-hydrophobic surface in the present invention; Fig.11 It is an electrochemical polarization curve diagram of the ultra-durable bionic heterogeneous super-hydrophobic surface in the present invention; Fig.12 This is the electrochemical impedance diagram of the ultra-durable bionic heterogeneous super-hydrophobic surface in the present invention. DETAILED DESCRIPTION
[0017] In order to better illustrate the preparation process involved in the present invention and its advantages over the prior art, the following Figure 1-12 Provide further explanation.
[0018] Embodiment 1 of the present invention:
[0019] like Figure 1 As shown, a method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing comprises the following steps: Step 1: Save the designed bionic microstructure surface model in stl. format. After slicing the bionic microstructure surface model, import it into the printing equipment control software BLT-MCS, turn on the water cooling cycle, install the substrate and scraper, place the Ti6Al4V spherical powder with a median diameter of 35μm in the printer powder bin, and then introduce high-purity argon gas into the printing chamber. After the oxygen content in the molding chamber is lower than 0.03%, use a laser power of 125W, a scanning speed of 600mm / s, a scanning spacing of 0.08mm, a layer thickness of 0.03mm, and a scanning angle of 47°. The strip scanning strategy begins to prepare the bionic microstructure surface. Each bionic microstructure unit in the bionic microstructure surface is a triangle, the base length of the triangle is 0.25mm, the height is 0.35mm, the microstructure height is 0.5mm, and a rotating cross array is performed to imitate the distribution of the lotus leaf papilla structure.
[0020] Step 2: The printed bionic microstructure surface is then immersed in a chemical polishing solution for polishing for 90 seconds to obtain a polished bionic microstructure surface of a pre-designed size; the chemical polishing solution is composed of H2O, HNO3, and HF in a volume ratio of 5:1:4, the HNO3 concentration is 4 mol / L, and the HF concentration is 22.5 mol / L.
[0021] Step 3: Disperse 4 g of nano-silica into 40 ml of anhydrous ethanol, stir for 5 minutes to make it uniformly dispersed, then add 1.5 g of perfluorodecyltrimethoxysilane solution, and stir in a constant temperature water bath at 40° C. for 2 hours to ensure that the nano-silica is fully modified; perform hydrophobic modification on the nano-silica particles to obtain a modified nano-silica dispersion; Step 4: Add 1.6 g polytetrafluoroethylene emulsion and 0.5 g KH550 solution to the modified nano-silica dispersion obtained in step 3 to form a sol, wherein KH550, as an organic and inorganic-friendly material, can serve as a "molecular bridge" to connect the organic polytetrafluoroethylene and the inorganic nano-silica; Step five, immersing the polished bionic microstructure surface in the sol for ultrasonic treatment for 30 minutes, and then placing it in a drying oven and drying it at 120°C for 6 hours to fully gelate it to obtain an ultra-durable bionic heterogeneous superhydrophobic surface.
[0022] Embodiment 2 of the present invention:
[0023] Experimental tests were conducted on the ultra-durable bionic heterogeneous super-hydrophobic surface obtained by the above method: Scanning electron microscopy characterization: The prepared ultra-durable bionic heterogeneous super-hydrophobic surface was characterized by scanning electron microscopy, such as Figure 2 As shown, the heterogeneous materials are well bonded and the nanofillers are evenly distributed, indicating that the preparation of the ultra-durable bionic heterogeneous superhydrophobic surface is successful.
[0024] (2) Contact angle test: The contact angle of the ultra-durable biomimetic heterogeneous super-hydrophobic surface was tested, such as Figure 3 As shown, the contact angle is as high as 171.555°, and it repels liquids of different densities.
[0025] Antifouling performance test: The antifouling properties of the ultra-durable biomimetic heterogeneous superhydrophobic surface were tested, e.g. Figure 4 As shown, carbon powder with high adhesion strength is sprinkled on the super-durable bionic heterogeneous super-hydrophobic surface. When water is dropped on the super-durable bionic heterogeneous super-hydrophobic surface with a dropper, it can be found that the carbon powder rolls down with the water droplets, indicating that the super-durable bionic heterogeneous super-hydrophobic surface has excellent anti-fouling properties.
[0026] Durability test: To test the durability of the super-durable bionic heterogeneous super-hydrophobic surface, a sandpaper abrasion test was first performed, e.g. Figure 5 As shown, the super-durable bionic heterogeneous super-hydrophobic surface is placed on 1000-mesh SiC sandpaper, and a weight of 500g is applied upward, and then reciprocated for 10cm as a cycle. It can be found that after 5000 cycles, the super-durable bionic heterogeneous super-hydrophobic surface still maintains the super-hydrophobic properties.
[0027] Compression test: The compression test machine was used to perform compression test on the ultra-durable biomimetic heterogeneous super-hydrophobic surface, e.g. Figure 6 As shown, when the compression displacement is 1 mm, the super-durable bionic heterogeneous super-hydrophobic surface can still maintain the super-hydrophobic properties.
[0028] (6) Friction and wear test under different loads: The friction and wear tests of the ultra-durable bionic heterogeneous super-hydrophobic surface under different loads were carried out, such as Figure 7 As shown in Figure 2, under a load of 1N, the friction curve of the ultra-durable bionic heterogeneous super-hydrophobic surface is very stable, and its average friction coefficient is reduced by 54.9% compared with the flat Ti6Al4V alloy. Figure 8 As shown in Figure 2, under a load of 5N, the friction and wear curve of the ultra-durable bionic heterogeneous super-hydrophobic surface fluctuated, but the overall friction coefficient was still reduced by 37.1%, as shown in Figure 2. Fig. 9 As shown in the figure, under a load of 10N, the friction and wear curve of the ultra-durable bionic heterogeneous super-hydrophobic surface is still lower than that of the flat Ti6Al4V alloy, down 15.2%. The ultra-durable bionic heterogeneous super-hydrophobic surface exhibits excellent low friction characteristics under all three loads. In addition, after the friction and wear test, we can Fig.10 It can be seen that even if the sample has deeper wear marks, it can still maintain its superhydrophobic properties.
[0029] (7) Electrochemical corrosion test: The electrochemical corrosion tests of the ultra-durable biomimetic heterogeneous superhydrophobic surface were carried out, e.g. Fig.11 As shown in the figure, compared with the planar Ti6Al4V alloy, the polarization curve of the ultra-durable bionic heterogeneous super-hydrophobic surface is significantly shifted downward, and the corrosion current density is reduced by about two orders of magnitude. The corrosion current density is an important indicator for evaluating corrosion resistance. The smaller the corrosion current density, the better the corrosion resistance. Fig.12 As shown, the capacitance ring radius of the super-durable bionic heterogeneous super-hydrophobic surface 8 is significantly larger than that of the planar Ti6Al4V alloy. The larger the capacitance ring radius, the better the corrosion resistance. The impedance of the super-durable bionic heterogeneous super-hydrophobic surface is increased by about 17 times, showing excellent corrosion resistance.
Claims
1. A method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing, characterized in that: The following steps are involved: Step 1: Use appropriate printing parameters and Ti6Al4V spherical powder as printing material to print the bionic microstructure surface in one step; Step 2, then immersing the bionic microstructure surface in a chemical polishing solution for polishing for 90 seconds to obtain a polished bionic microstructure surface of a pre-designed size; Step 3, performing hydrophobic modification on the nano-silicon dioxide particles to obtain a modified nano-silicon dioxide dispersion; Step 4, adding polytetrafluoroethylene solution and KH550 solution to the modified nano-silicon dioxide dispersion obtained in step 3 to form a sol; Step 5, immersing the polished bionic microstructure surface obtained in step 2 into the sol of step 4, and drying after ultrasonic treatment to gel it to obtain an ultra-durable bionic heterogeneous super-hydrophobic surface.
2. The method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing according to claim 1, characterized in that: The bionic microstructures are triangular and arranged in a cross array to imitate the distribution of lotus leaf papillary structures.
3. The method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing according to claim 1, characterized in that: In the step 1, the specific method for printing the bionic microstructure surface is as follows: saving the designed bionic microstructure surface model in stl. format, slicing the bionic microstructure surface model and importing it into the printing equipment control software, turning on the water cooling cycle, installing the substrate and the scraper, placing Ti6Al4V spherical powder with a median diameter of 35 μm in the printer powder bin, and then introducing high-purity argon gas into the printing chamber. After the oxygen content in the molding chamber is lower than 0.03%, a strip scanning strategy with a laser power of 125 W, a scanning speed of 600 mm / s, a scanning spacing of 0.08 mm, a layer thickness of 0.03 mm, and a scanning angle of 47° is used to start preparing the bionic microstructure surface.
4. The method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing according to claim 1, characterized in that: In the step 2, the chemical polishing solution is composed of H2O, HNO3, and HF in a volume ratio of 5:1:4, the concentration of HNO3 is 4 mol / L, and the concentration of HF is 22.5 mol / L.
5. The method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing according to claim 1, characterized in that: In the step 3, the specific method for hydrophobic modification of the nano-silica particles is as follows: 4 g of nano-silica is dispersed in 40 ml of anhydrous ethanol, stirred for 5 minutes to make it uniformly dispersed, and then 1.5 g of perfluorodecyltrimethoxysilane solution is added, and stirred in a constant temperature water bath at 40°C for 2 hours to ensure that the nano-silica is fully modified.
6. The method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing according to claim 1, characterized in that: In the step 4, the specific method for forming the sol is: adding 1.6 g of polytetrafluoroethylene emulsion and 0.5 g of KH550 solution to the modified nano-silicon dioxide dispersion obtained in the step 3 to form a sol.
7. The method for preparing a super-durable bionic heterogeneous super-hydrophobic surface based on additive manufacturing according to claim 1, characterized in that: In the step 5, the specific method for obtaining the ultra-durable bionic heterogeneous super-hydrophobic surface is as follows: immersing the polished bionic microstructure surface in a sol for ultrasonic treatment for 30 minutes, and then placing it in a drying oven at 120° C. for 6 hours to fully gelate it to obtain an ultra-durable bionic heterogeneous super-hydrophobic surface.
Citation Information
Patent Citations
Preparation method of SiO2 / polytetrafluoroethylene hybridized super-hydrophobic coating
CN103964701A
Transparent super-hydrophobic coating material and method for preparing transparent super-hydrophobic coating by transparent super-hydrophobic coating material
CN104449357A
Super-hydrophobic material and preparation method thereof
CN106975588A
Durable super-hydrophilic or super-hydrophobic plastic surface and preparation method thereof
CN109251345A
Super-hydrophobic bionic anti-corrosion material and preparation method thereof
CN118064057A
Cited By
Preparation method of bionic wear-resistant composite structure for railway turnout slide plate
CN120325998A